Autophagy and Skin Diseases - Klapan, Kim; Simon, Dagmar; Karaulov, Alexander; Gomzikova, Marina; Rizvanov, Albert; Yousefi, Shida; Simon, Hans-Uwe (Frontiers in Pharmacology, 2022)
Autophagy is a highly conserved lysosomal degradation system that involves the creation of autophagosomes, which eventually fuse with lysosomes and breakdown misfolded proteins and damaged organelles with their enzymes. Autophagy is widely known for its function in cellular homeostasis under physiological and pathological settings. Defects in autophagy have been implicated in the pathophysiology of a variety of human diseases. The new line of evidence suggests that autophagy is inextricably linked to skin disorders. This review summarizes the principles behind autophagy and highlights current findings of autophagy's role in skin disorders and strategies for therapeutic modulation.